L’écriture artiste des maîtres de ballet à propos des programmes du ballet pantomime - Juan Ignacio Vallejos (Les Dossiers du GRIHL)
The development of ballet pantomime is strongly linked to a written culture. Moreover, the ballet programs operate as intervention tools for ballet masters in public space. Their writing embodies an artistic and social project, which is linked to a revaluation of the art of dance and the ballet master’s work. The assertion of new poetic ideas is then associated with upward social mobility strategies in the context of a redefinition of aristocratic prestige.